Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\sin^3 x=\frac{3}{4}\sin x - \frac{1}{4}\sin 3x$$

Is there any formula that tells this or why is it like that?

share|cite|improve this question
Certainly‌​. – J. M. Jan 9 '12 at 16:34
Expand $$\sin 3x = \sin(x+2x) = \sin x \cos 2x + \cos x\sin 2x = \sin x(\cos^2 x - \sin^2 x) + 2\sin x \cos^2 x$$ and set $\cos^2 x = 1 - \sin^2 x$ – Dilip Sarwate Jan 9 '12 at 16:47
up vote 9 down vote accepted

\begin{align} \sin(3x) &= \sin(x+2x) \tag{1} \\ \sin(\alpha+\beta) &= \sin \alpha \cdot \cos \beta + \cos \alpha \cdot \sin \beta \tag{2} \\ \sin 2\alpha &= 2\cdot \sin \alpha \cdot \cos \alpha \tag{3} \\ \cos 2\alpha &= \cos^2 \alpha - \sin^2 \alpha \tag{4} \\ 1 &= \sin^2 \alpha + \cos^2 \alpha \tag{5} %% \end{align}

If you apply all these formulas you should get:

$$ \sin(3x)=3\cdot \sin x -4\cdot \sin^3 x $$

share|cite|improve this answer
It's not $sin(3x)$, it's $sin^3(x)$ – Andrew Jan 9 '12 at 16:54
@Andrew,I am sure that you know how to express $\sin^3 x$ from the last equality . – pedja Jan 9 '12 at 16:57
@Andrew: $sin(3x)=3sinx-4sin^3x => sin^3x = \frac{3}{4}sinx - \frac{1}{4}sin3x $ – GSBabil Jan 10 '12 at 3:30

$$\sin(3x)=\Im(\mathrm e^{3\mathrm ix})=\Im\left((\cos(x)+\mathrm i\sin(x))^3\right)$$

$$(\cos(x)+\mathrm i\sin(x))^3=\cos^3(x)+3\mathrm i\ \cos^2(x)\sin(x)-3\cos(x)\sin^2(x)-\mathrm i\ \sin^3(x)$$

$$\sin(3x)=3\ \cos^2(x)\sin(x)-\sin^3(x)=3\sin(x)-4\sin^3(x)$$

$$4\ \sin^3(x)=3\sin(x)-\sin(3x)$$

Exercise Likewise, show that

$$16\ \sin^5(x)=\sin(5x)-5\sin(3x)+10\sin(x)$$

Added The other way round (this one generalizes easily and explains the appearance of the binomial coefficients $(1,3)$ for $\sin^3$ and $(1,5,10)$ for $\sin^5$):

$$(2\mathrm i\sin(x))^3=(\mathrm e^{\mathrm ix}-\mathrm e^{-\mathrm ix})^3=\mathrm e^{3\mathrm ix}-3\mathrm e^{\mathrm ix}+3\mathrm e^{-\mathrm ix}-\mathrm e^{-3\mathrm ix}$$ $$ (-8\mathrm i)\ \sin^3(x)=(2\mathrm i)\ (\sin(3x)-3\sin(x)) $$ $$ -4\ \sin^3(x)=\sin(3x)-3\sin(x) $$

share|cite|improve this answer
It's not $sin(3x)$, it's $sin^3(x)$ – Andrew Jan 9 '12 at 16:55
@Andrew Didier's last line gives the required equality. – David Mitra Jan 9 '12 at 17:13

Continuing from my comment to bgins's answer, one can start from the (defining) Chebyshev polynomial identity


and make the substitution $x=\frac{\pi}{2}-z$ to yield the identity


(use the addition formula and mind the values of cosine and sine at integer multiples of $\pi$.)

Now, there is the identity

$$T_{2n-1}(u)=\sum_{m=0}^{n-1} (-1)^{n+m+1}\frac{2n-1}{2m+1}\binom{n+m-1}{2m} 4^m u^{2m+1}$$

which can be used to derive the matrix-vector identity

$$\begin{pmatrix}\sin\,x\\\sin\,3x\\\vdots\\\sin((2n-1)x)\end{pmatrix}=\mathbf L\mathbf D\begin{pmatrix}\sin\,x\\\sin^3 x\\\vdots\\\sin^{2n-1}x\end{pmatrix}$$

where the diagonal matrix $\mathbf D$ has the diagonal entries $d_{k,k}=(-4)^{k-1}$ and the unit lower triangular matrix $\mathbf L$ has the entries $\ell_{j,k}=\dfrac{2j-1}{2k-1}\dbinom{j+k-2}{2k-2}$. Inverting this relation gives

$$\begin{pmatrix}\sin\,x\\\sin^3 x\\\vdots\\\sin^{2n-1}x\end{pmatrix}=\mathbf D^{-1}\mathbf W\begin{pmatrix}\sin\,x\\\sin\,3x\\\vdots\\\sin((2n-1)x)\end{pmatrix}$$

where $\mathbf W=\mathbf L^{-1}$ is also a unit lower triangular matrix with entries $w_{j,k}=(-1)^{j+k} \dbinom{2j-1}{j+k-1}$. (The proof that $\mathbf L\mathbf W=\mathbf I$ is not too hard, and is left as an exercise.) In particular, the second row yields the OP's desired identity.

share|cite|improve this answer

de Moivre's formula says $$ \begin{align} \cos(3x)+i\sin(3x) &=(\cos(x)+i\sin(x))^3\\ &=\left(\cos^3(x)-3\cos(x)\sin^2(x)\right)+i\left(3\cos^2(x)\sin(x)-\sin^3(x)\right)\\ &=\left(4\cos^3(x)-3\cos(x)\right)+i\left(3\sin(x)-4\sin^3(x)\right)\tag{1} \end{align} $$ Therefore, $$ \begin{align} \cos(3x)&=4\cos^3(x)-3\cos(x)\tag{2}\\ \sin(3x)&=3\sin(x)-4\sin^3(x)\tag{3} \end{align} $$ Solving $(3)$ for $\sin^3(x)$ yields $$ \sin^3(x)=\frac34\sin(x)-\frac14\sin(3x)\tag{4} $$

share|cite|improve this answer

Here is a mild generalization.

Let $X,Y\ $ be indeterminates, and let $f(X;Y)\in\mathbb C[X,Y\ ]$ be a polynomial.

The following observations give a purely algebraic method to decide if we have $$f(\cos t\,;\sin t)=0$$ for all $t$ in $\mathbb R$.

If $U,V,T$ are other indeterminates, then the following conditions are equivalent:

(a) $\ f(\cos t\,;\sin t)=0$ for all $t$ in $\mathbb R$,

(b) $\ X^2+Y^2-1$ divides $f(X;Y)$,

(c) $\ UV-1$ divides $$g(U,V):=f\left(\frac{U+V}{2}\ ;\ \frac{U-V}{2i}\right),$$

(d) $\ g(T,T^{-1})=0$.

The interpretation of the indeterminates $X,Y,U,V,T$ can be informally expressed by the equalities $$ X=\cos t,\quad Y=\sin t,\quad T=U=e^{it},\quad T^{-1}=V=e^{-it}. $$

share|cite|improve this answer

You might want to look at Chebyshev polynomials of the first and second kind, denoted $T_n$ and $U_n$ respectively, which are defined recursively by $$ \begin{matrix} T_0 = 1,& T_1(x) = x,& T_{n+1} = 2x T_n(x) - T_{n-1}(x) \\ U_0 = 1,& U_1(x) = 2x,& U_{n+1} = 2x U_n(x) - U_{n-1}(x) \end{matrix} $$ (hence each of degree $n$) and give the formulas $$ \cos(n\theta) = T_n(\cos\theta), \qquad \frac{\sin\left((n+1)\theta\right)}{\sin\theta} = U_n(\cos\theta), $$ and have various closed form expressions, for example involving binomial coefficients.

share|cite|improve this answer
In particular, $T_{2n-1}(\sin\,z)=(-1)^{n+1}\sin((2n-1)z)$ – J. M. Jan 10 '12 at 3:46

If you're ever unsure of a trig identity, just convert it to complex exponentials and expand. It's especially nice if you have a CAS that can do the expansion for you (or if you're just handy with such things).

$\sin^3(x) = \left (\frac{e^{i x} - e^{-i x}}{2i}\right )^3 = \frac{e^{3ix}-3e^{ix}+3e^{-ix}-e^{-3ix}}{-8i}$ and $\frac{3}{4}\sin(x) - \frac{1}{4}\sin(3x) = \frac{3}{4}\left (\frac{e^{i x} - e^{-i x}}{2i}\right ) - \frac{1}{4}\left (\frac{e^{3i x} - e^{-3i x}}{2i}\right ) = \frac{e^{3ix}-3e^{ix}+3e^{-ix}-e^{-3ix}}{-8i}$.

Alternately, we could derive the right hand side by converting the exponentials back to sines and cosines using $e^{ix} = \cos(x) + i\sin(x)$ and canceling.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.